Analysis of the Influence of Financial Literacy on Investment Decisions of MSME Actors in Kupang City, NTT with RIsk Tolerance as a moderation variable - Janri Manafe; Tuti Setyorini; Ryonaldo Hattu (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study examines the influence of financial literacy on the investment decisions of micro, small, and medium enterprises (MSMEs) in Kupang City, with risk tolerance as a moderating variable. Using a quantitative, explanatory approach, data were collected from 105 MSME actors through purposive sampling. Respondents completed a structured questionnaire, and the data were analyzed using Moderated Regression Analysis (MRA). The results show that financial literacy has a positive and significant effect on investment decisions. Risk tolerance also demonstrates a significant positive effect and strengthens the relationship between financial literacy and investment decisions. These findings highlight the importance of combining financial knowledge with psychological readiness to take risks. Practically, the study suggests the need for integrated financial literacy programs that also foster risk management skills to support more rational and sustainable investments.